ESTUDO DA APLICAÇÃO DE NANOTUBOS DE CARBONO EM CAMADAS INFERIORES DE PAVIMENTOS FLEXÍVEIS - Loures, Fábio Santos da Rocha (2022)
According to the latest statistical yearbook of the National Transport Confederation (CNT, 2021), in Brazil, only 12% of roads are paved, the vast majority of which consist of flexible pavements, largely of low quality, resulting in an overload of the road network and increasing the risk of accidents. Due to the excellent results obtained, in several engineering fields, with the use of nanomaterials, one of the possible solutions to increase the useful life of these pavements could be the use of Carbon Nanotubes (NTCs) in their structure. In this context, the present work aimed to develop and characterize a nanocomposite (NC) with CNTs and clayey soil in order to improve the Brazilian road system. The CNTs were prepared by the chemical vapor deposition (CVD) method, and the NC by the simple mixture of CNTs with kaolinitic clayey soil (0.5 - 2.0% w/w). The materials were characterized by geotechnical tests (Granulometry, Mini-CBR and Consistency Tests), physical-chemical tests (SEM, N2 Porosimetry and FTIR), as well as by an initial theoretical study of classical modeling (molecular dynamics). Through the Mini-CBR tests, an increase in the shear strength of the nanocomposite was observed, indicating a positive influence of the incorporation of CNTs on the clayey soil. The results of the Limits of Consistency and of the modeling reinforced those obtained by the Mini-CBR method due to the decrease in the value of the Plasticity Index (IP) and the reduction of the average distances of equilibrium between the components of the nanocomposite after the addition of CNTs. Therefore, the present results were considered promising since a positive signal of its application in flexible pavements could represent a great advance, especially with regard to the aspects of economy and safety, in the execution of road works.